Establishment and Optimization of Micropropagation System for Southern Highbush Blueberry - Yuting Wang; Xiaoyun Zhang; Zhehao Jiang; Xiaolong Yang; Xiaojuan Liu; Xi Ou; Wei Su; Riyuan Chen (Horticulturae, 2023)
The optimization of micropropagation for blueberries is crucial due to the growing blueberry industry and demand for plantlets. This study focused on four stages: explant sterilization, in vitro establishment, in vitro proliferation, and ex vitro rooting, aiming to establish an efficient in vitro propagation system for southern highbush blueberry cultivar ‘ZY09’. The most effective explant sterilization method was a 60 s treatment with 75% ethanol and a 5 min treatment with 4% NaClO. During the establishment of the in vitro culture, the modified woody plant medium was found to be suitable. The replacement of NH4NO3 in woody plant medium with (NH4)2SO4 facilitated the proliferation of blueberry microshoots. The optimal combination of plant growth regulators for the in vitro proliferation of blueberry microshoots was indole-3-butyric acid (0.1 mg·L−1), thidiazuron (0.0005 mg·L−1), and zeatin (1 mg·L−1). Perlite was the most suitable substrate for ex vitro rooting. The best ex vitro rooting performance was observed without immersion in growth regulators. Indole-3-butyric acid enhances root formation and suppresses root elongation in blueberries. The findings of this study can be applied to large-scale in vitro propagation of southern highbush blueberry and provide a reference for the genetic transformation of blueberries.